The effect of different potharvest technologies to extend market life of table grape cultivars - Mylona, Maria (n/a, 2019)
Grapes are widely used as fresh fruits (table grapes) as well as processed in the form of wine, grape juice and raisins. These fruits are non-climacteric which means that their maturation as well as their qualitative characteristics are developed while they are still on the plant. One of their main characteristics is their short post-harvest life. Grapes, as fresh fruits are very sensitive and the loss during storage and distribution is particularly high. Research studies have focused on extending the shelf life with optimal organoleptic properties of the product, with the use of modified atmosphere packaging. Additionally, most of the studies choose the use of the ratio of additional gases for balancing the safe shelf life extension. Recently, the demand for table grapes has been increasing and consumers are becoming more demanding in regards to the quality of the table grapes. Therefore, the main aim of the present study was the evaluation of the qualitative features of seven varieties of table grapes (such as “Prime”, “Cardinal”, “Superior”, “Τhompson”, “Red Globe”, “Verico”, “Crimson”) with successive maturation that are grown in Cyprus. Furthermore, the extension of the post-harvest life of the variety “Verico” in ‘passive modified atmosphere’ packaging for forty days was also examined. The fruits of each variety were harvested during the period of commercial maturity of each variety. Firstly, the weight of the stems and grapes were measured as well as the amount of berries for each variety; then, the total soluble solid ingredients (T.S.S.), the tartaric acidity and the properties of the texture were identified. Additionally, the colour of the outer fruit was determined on representative samples of each variety. The results showed that the fruits of the seedless variety “Crimson”, which was harvested last (19th of October), had the highest percentage of total soluble solid ingredients (22.86 %). For all the seven varieties observed, it was noted that the T.S.S. vary depending on the variety and the harvesting period. At this point, it is worth pointing out that the “Thompson” variety, which was harvested on 23 of August had 19.26% T.S.S. Therefore, it had the highest sugar amount among the premature varieties. Furthermore, as expected, the premature grape varieties (such as “Prime”) had a titratable acidity of 0.84 % compared to the more late varieties that had acidity of about 0.30 %. As part of the present study, the colour of representative grapes and the consistency of their flesh were also examined. Among the white and pigmented varieties, the brightest colour was identified in the “Superior” and the “Verico” respectively which presented the highest L* value. The consistency of the flesh for the white as well as the coloured varieties was between 4.86 N and 7.25 N on average. However, the “Prime” and “Red Globe” had the highest values with 7.25 N and 7.14 N respectively. Additionally, in regards to the preservation of the fruits of the “Verico” variety in ‘passive modified atmosphere packaging’ in 2°C for a forty days the results show that this preservation method has positively impacted the consistency of the flesh of the grapes as it was observed that when they were preserved in MAP, the average value was higher compared to the average value in non-modified atmosphere. In addition, as expected in a non-climacteric fruit such as grape there were no noticeable changes identified in the T.S.S and Titratable acidity. Also, it is important to note that the colour of the grapes was brighter after forty days of preservation in 2°C in the grapes that were not in MAP. Overall, in the present study, after an initial exploration of the qualitative characteristics of the table varieties that are grown in Cyprus, the qualitative features (sugars, acidity, coherence and colour of the grapes) are varying depending on the harvesting period, the maturity stage, the cultivation practices, the climate etc. The results are in line with the results of similar studies in other countries. Also, the findings of this study indicate that for a non-climacteric fruit and more specifically the “Verico” variety, the post-harvest preservation practices that occur in the fruit as it is preserved in freezing conditions in passive modified atmosphere packaging, were not statistically significant. Nevertheless, this late variety could potentially be a good choice for research after harvesting achieving high market prices at the end of the harvesting period of the Cypriot grapes.
Keywords: table grapes; postharvest; quality attributes